(untitled) (Ukrainian Journal of Ophthalmology, 2025)
World-renowned ophthalmologist Jack J. Kanski passed away on January 5, 2019. He was a living legend in ophthalmology and left behind an unforgettable and invaluable legacy. “Clinical Ophthalmology: A Systematic Approach”, the book written by this talented person, has been a bible of ophthalmology for medical students and ophthalmologists throughout recent decades. He authored more than 30 textbooks on various aspects of eye disease including cataract, glaucoma, uveitis, retinal and pediatric eye disorders.